Г) (3 7/2 + 2) (4 - 2 * 3 7/3 + 3 14/3) = (5 7/2) * (4 - 6 14/3 + 3 14/3) = 17/2 * (4 -3 14/3) = 17/2 * (12/3 - 23/3) = 17/2 * (- 11/3) = - 187/6 = - 31 1/6
Ответ:
65/14
Пошаговое объяснение:
4 9/14= мы 4 × 14 +9= 65 и прибавляем дробь 14. получается ответ 65/14
А) х+23=50
х=23+50
х=73
б) 8+z=17
z=17-8
z=9
в) u-25=0
u= 25+0
u = 25
Ответ:
Пошаговое объяснение:
1) 12 1/8 - 5 5/16 = 12 2/16 - 5 5/16 = 6 13/16
2) 6 13/16 + 3 1/4 = 6 13/16 + 3 4/16 = 9 17/16 = 10 1/16
3) 10 1/16 : (-13 5/12) = 161/16 * (-12/161) = -3/4
4) -3/4 + 6,35 = -3/4 + 6 7/20 = 6 7/20 - 15/20 = 5 12/20 = 5 3/5
5) 2 2/3 + 3/5 = 2 10/15 + 9/15 = 2 19/15 = 3 4/15
6) 3 4/15 * (-2 1/7) = 49/15 * (-15/7) = -7
7) 5 3/5 : (-7) = 28/5 * (-1/7) = -4/5